Regulation of CXCR6 Expression on Adipocytes and Osteoblasts Differentiated from Human Adipose Tissue-Derived Mesenchymal Stem Cells - Seung-Cheol Lee; Yoo-Jung Lee; Min Kyoung Shin; Jung-Suk Sung (Hindawi Limited, 2020)
Human mesenchymal stem cells derived from adipose tissue (hADMSCs) are a desirable candidate in regenerative medicine. hADMSCs secrete growth factors, cytokines, and chemokines and also express various receptors that are important in cell activation, differentiation, and migration to injured tissue. We showed that the expression level of chemokine receptor CXCR6 was significantly increased by ~2.5-fold in adipogenic-differentiated cells (Ad), but not in osteogenic-differentiated cells (Os) when compared with hADMSCs. However, regulation of CXCR6 expression on hADMSCs by using lentiviral particles did not affect the differentiation potential of hADMSCs. Increased expression of CXCR6 on Ad was mediated by both receptor recycling, which was in turn regulated by secretion of CXCL16, and de novo synthesis. The level of soluble CXCL16 was highly increased in both Ad and Os in particular, which inversely correlates with the expression on a transmembrane-bound form of CXCL16 that is cleaved by disintegrin and metalloproteinase. We concluded that the expression of CXCR6 is regulated by receptor degradation or recycling when it is internalized by interaction with CXCL16 and by de novo synthesis of CXCR6. Overall, our study may provide an insight into the molecular mechanisms of the CXCR6 reciprocally expressed on differentiated cells from hADMSCs.